Positioning Latin America within the southern turn in planning: perspectives on an "Emerging field". Conclusion to the special issue on Latin America. - Galland, Daniel; Elinbaum, Pablo (Routledge, 2018)
The conclusion to this special issue on the state of planning in Latin America provides a series of critical reflections based on the cross-comparative analysis of its seven contributions. Rather than summarising the results embedded in the survey, the authors allude to the thematic questions posed in the introduction by responding with thought-provoking, argument-based counter-questions as revealed by each of the section headings comprising this conclusion. To make a contribution towards positioning planning in Latin America as an emerging "field" within the Southern turn in planning, the following sections suggest a series of research trajectories whose underlying rationales build on the exposed perceptions around significant planning problems across the region.
Keywords: Stadtentwicklungsplanung; Stadtplanung; Raumplanung; Planungssystem; Planungspraxis; Planungstheorie; Planerausbildung; Internationaler Vergleich; Überblick